DIGITAL TALE MEDIA TO IMPROVE THE EMOTIONAL INTELLIGENCE OF ELEMENTARY SCHOOL - Herlinda Ayu Safitri; Murfiah Dewi Wulandari (Auladuna: Jurnal Pendidikan Dasar Islam, 2023)
Abstract This study aims to determine the effectiveness of digital tale media and the impact of its use on students' emotional intelligence. This study used a quantitative approach with the quasi-experimental method and nonequivalent control group design. The research sample consisted of 40 students of SD Negeri Mojolegi (20 students from each class IIIA and IIIB). Both groups received a pretest and a posttest. Data collection also used a closed questionnaire. The results of this study revealed that the use of digital tale media was quite effective in improving the emotional intelligence of elementary school students, especially in the lower grades. Gradually giving fairy tales helped to improve emotional intelligence by looking at the attitudes and behaviour of the characters of the tales so students can show and develop their emotions. Thus, teachers can provide material in stages in the form of digital tales with different themes to improve students' emotional intelligence.